Benzocaine and Eugenol as anesthetics for pangasius juveniles, Pangasianodon hypophthalmus - A. F. Leonardo; H. P. Barros; G. G. Sampaio (Boletim de Indústria Animal, 2022)
The aim of this study was to evaluate the effect and efficacy of different concentrations of eugenol and benzocaine for pangasius juveniles (Pangasianodon hypophthalmus) and determine the anesthetic and concentration most appropriate for carrying out routine fish farming practices for this species. One hundred juveniles with an average weight of 32.10 ± 4.9 g and an average total length of 15.32 ± 0.57 cm were used. Four concentrations of both anesthetics were evaluated: 0, 25, 50, 75 and 100 mg/L, with four induction time stages and three recovery stages. During the time that the fish remained anesthetized, biometric procedures were performed. Then, they were transferred to a 10-liter aquarium containing clean water, without adding the anesthetic to observe the recovery time. After recovery, the animals were kept in aquariums for 72 hours to check for mortality. Eugenol, at all concentrations evaluated, and benzocaine, at a concentration of 25 mg/L, were not effective in sedating juveniles of pangasius. Benzocaine concentrations of 75 and 100 mg/L were effective for anesthesia and recovery of fish within the time span of five and seven minutes. However, considering animal welfare, the use of a concentration of 100 mg/L is recommended, as it resulted in shorter latency and recovery times.